Analisis Dampak Otonomi Khusus dalam Upaya Optimalisasi Sektor Pendidikan di Provinsi Papua - Zainul Rahman; Dede Sri Kartini (Universitas Sebelas Maret, 2023)
The presence of the Special Autonomy Law for the Province of Papua is a positive stimulant to bring about prosperity in the education sector. However, so far it has been found that the education sector is one of the sectors that has not run optimally. Special autonomy, which has not had a significant impact on the education sector, has created disparities in education between Papua Province and other regions in Indonesia. Based on this, this study seeks to examine the impact of the special autonomy policy on optimizing the education sector in Papua Province. This study uses a qualitative approach with a descriptive analysis model. The main data in this study comes from literature studies. The results of this study found that special autonomy has not had a significant impact on the people of Papua. This can be seen from the IPM of Papua Province which is at the bottom of the national standings. On the other side, the Papuan community's school enrollment rates and average length of schooling are still far below the national APS and RLS. This means that special autonomy has not been able to bring optimal impact on the education sector. There are several inhibiting factors, including the lack of political will from the Papua Provincial Government, the existence of corrupt practices, the lack of involvement of the Papuan People's Council in evaluating the allocation of autonomy funds in particular, including in evaluating the allocation of funds for the education sector and due to the contours of the area being quite large and difficult.